The influence of high pressure processing on antimutagenic activities of fruit and vegetable juices - Butz, Peter; Edenharder, Rudolf; Fister, Heike; Tauscher, Bernhard (Food research international, 1997)
In model experiments using the Salmonella/reversion assay (Ames test) and the carcinogen 2-amino-3-methyl-imidazo[4,5-f]quinoline (IQ), antimutagenic activities against IQ had been detected in about 70% of 62 fruit and vegetable species [Edenharder, Kurz, John, Burgard and Seeger (1994) Fd Chem. Toxic. 32, 443-459]. However, thermal stability of the antimutagenic factors varied considerably. As hydrostatic pressure is an alternative to heat in food processing and preservation, homogenates of 14 fruit and vegetable species were exposed to different pressures and temperatures. According to the response of the antimutagenic potential, three groups of produce could be identified: (a) moderate antimutagenic potencies in grapefruit and strawberries were resistant to both heat and pressure; (b) moderate to strong antimutagenic potencies in carrots, cauliflower, kohlrabi, leek, and spinach were more or less sensitive to heat, but not to pressure; (c) antimutagenic activities of beet and tomatoes were affected by extreme pressure only (600 MPa, 50 °C; 800 MPa, 35 °C). These results should be relevant for the (industrial) processing of horticultural produce as, according to epidemiological studies, diets rich in fruit and vegetables are associated with a low incidence of human cancer.
Online verfügbar: 25. Februar 1998
Gesehen am 12.02.2026